The modernist imagination : intellectual history and critical theory : essays in honor of Martin Jay - Breckman, Warren, 1963-; Jay, Martin, 1944- (Berghahn Books, 2009)
"Some of the most exciting and innovative work in the humanities currently takes place at the intersection of intellectual history and critical theory. Just as critical theorists are becoming more aware of the historicity of theory, contemporary practitioners of modern intellectual history are recognizing their potential contributions to theoretical discourse. No one has done more than Martin Jay to realize the possibilities for mutual enrichment between intellectual history and critical theory. This carefully selected collection of essays addresses central questions and current practices of intellectual history and asks how the legacy of critical theory has influenced scholarship across a wide range of scholarly disciplines. In honor of Martin Jay's unparalleled achievements, this volume includes work from some of the most prominent contemporary scholars in the humanities and social sciences."--Jacket